2021
DOI: 10.3389/fgene.2021.737656
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of the Expression Characteristics, Prognostic Value, and Immune Characteristics of PPARG in Breast Cancer

Abstract: Background: Breast cancer (BRCA) is the most frequent malignancy. Identification of potential biomarkers could help to better understand and combat the disease at early stages.Methods: We selected the overlapping genes of differential expressed genes and genes in BRCA-highly correlated modules by Weighted Gene Co-Expression Network Analysis (WGCNA) in TCGA and GEO data and performed KEGG and GO enrichment. PPARG was achieved from Protein-Protein Interaction (PPI) network analysis and prognostic analysis. TIMER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Sufficient evidence supported that PPARG augmentation has a positive impact on multiple significant pathological processes in depression. [ 29 ] It was demonstrated that PPARG was a potential biomarker of BC and its gene expression was associated with BC prognosis, [ 30 ] although our prognosis analysis did not reach consistent results due to the stricter screening thresholds. Blocking PPARG interaction facilitates nuclear receptor subfamily 4 group A member 1 interdiction of fatty acid uptake and suppresses BC progression.…”
Section: Discussionmentioning
confidence: 70%
“…Sufficient evidence supported that PPARG augmentation has a positive impact on multiple significant pathological processes in depression. [ 29 ] It was demonstrated that PPARG was a potential biomarker of BC and its gene expression was associated with BC prognosis, [ 30 ] although our prognosis analysis did not reach consistent results due to the stricter screening thresholds. Blocking PPARG interaction facilitates nuclear receptor subfamily 4 group A member 1 interdiction of fatty acid uptake and suppresses BC progression.…”
Section: Discussionmentioning
confidence: 70%
“…High expression of PPARγ was signi cantly associated with improved prognosis (20). Besides, study shows miR-494 upregulation was signi cantly associated with PTEN downregulation and inhibition of miR-494 suppressed cell proliferation and growth by directly targeting the 3'-untranslated region (3'-UTR) of PTEN mRNA (21).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was performed using R version 4.1.2, and GraphPad Prism 8.0 ( Wang Q. et al, 2021 ; Wu et al, 2021 ; Fang et al, 2022 ; Liu et al, 2022 ). Each experiment was repeated independently a minimum of three times.…”
Section: Methodsmentioning
confidence: 99%